Do primary care professionals agree about progress with implementation of primary care teams: results from a cross sectional study. Issue 1 (December 2016) - Tierney, E.; O'Sullivan, M.; Hickey, L.; Hannigan, A.; May, C.; Cullen, W.; Kennedy, N.; Kineen, L.; MacFarlane, A.
Abstract Background Primary care is the cornerstone of healthcare reform with policies across jurisdictions promoting interdisciplinary team working. The effective implementation of such health policies requires understanding the perspectives of all actors. However, there is a lack of research about health professionals' views of this process. This study compares Primary Healthcare Professionals' perceptions of the effectiveness of the Primary Care Strategy and Primary Care Team (PCT) implementation in Ireland. Methods Design and Setting: e-survey of (1) General Practitioners (GPs) associated with a Graduate Medical School (N = 100) and (2) Primary Care Professionals in 3 of 4 Health Service Executive (HSE) regions (N = 2309). After piloting, snowball sampling was used to administer the survey. Descriptive analysis was carried out using SPSS. Ratings across groups were compared using non-parametric tests. Results There were 569 responses. Response rates varied across disciplines (71 % for GPs, 22 % for other Primary Healthcare Professionals (PCPs). Respondents across all disciplines viewed interdisciplinary working as important. Respondents agreed on lack of progress of implementation of formal PCTs (median rating of 2, where 1 is no progress at all and 5 is complete implementation). GPs were more negative about the effectiveness of the Strategy to promote different disciplines to work together (median rating of 2 compared to 3 for clinical therapists and 3.5 for nurses, P = 0.001). Respondents identified resources and GP participation as most important for effective team working. Protected time for meetings and capacity to manage workload for meetings were rated as very important factors for effective team working by GPs, clinical therapists and nurses. A building for co-location of teams was rated as an important factor by nurses and clinical therapists though GPs rated it as less important. Payment to attend meetings and contractual arrangements were considered important factors by GPs but not by nurses or clinical therapists. Conclusion PCPs and GPs agree there is limited PCT implementation. GPs are most negative about this implementation. There is some disagreement about which resources are most important for effective PCT working. These findings provide valuable data for clinicians and policy makers about implementation of interdisciplinary teams in primary care.